Computer games to teach deaf children in literacy acquisition - Boscarioli, Clodis; Baqueta, Jeferson José; de Aguiar Soares, Rosiene Queres; Colling, João Paulo; Zabot, Guilherme Felipe (Revista Vínculos, 2016)
Educational games ought to be support instruments providing elements that contribute to reinforcing previously learned school subjects. This paper discusses the use of educational games when teaching deaf children, and the importance of visual resources, such as images and videos, at building their knowledge. It also presents Conceitos, a game oriented to deaf children in their literacy development that aids the learning of everyday concepts both in Sign Language and written Portuguese, by means of interactions with tridimensional objects.